76.4k views
1 vote
Rewrite the function by completing the square.
f(x) = x^2 - 14x +63

User Jon Thoms
by
4.6k points

1 Answer

4 votes

Answer:


f(x)=(x-7)^2+14

Explanation:

The complete square of this would be
x^2-14x+49, since then that would be just
(x-7)^2. Therefore, you can rewrite the function like this:


f(x)=(x^2-14x+49)+14\\f(x)=(x-7)^2+14

Hope this helps!

User IBelieve
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.